Clinical, electromyographic, and biophysical characterization of the rare Nav1.4 channel mutation SCN4A L1436P - Wang, François Charles; Bouquiaux, Olivier; Lievens, Isabelle; Lakaye, Bernard; Vandries, Laura; Poleur, Margaux; Abdou Ide, Samira; Inci, Nurcan; Seutin, Vincent (Frontiers in Physiology, 2025)
IntroductionOur aims were to provide an integrated clinical and biophysical characterization of the rare variant NM_000334.4(SCN4A) c.4307T>C (p.Leu1436Pro; L1436P), affecting the skeletal muscle sodium channel Nav1.4, and to compare its functional consequences with both wild-type (WT) channels and the well-established pathogenic variant p.Arg1448His (R1448H).MethodsWe retrospectively analyzed nine unrelated patients carrying the heterozygous L1436P variant. Clinical evaluation included neurological examination and standardized electrodiagnostic protocols. Electromyographic studies were performed at baseline and after muscle cooling. In addition, the biophysical characteristics of the mutant channels were compared to those of WT channels and R1448H, using whole-cell patch clamp recordings of hNav1.4 currents in stably transfected HEK293 cells. Recordings were performed at near physiological temperature (32°C), room temperature (22°C) and cold temperature (15°C).ResultsThe clinical phenotypes associated with this SCN4A mutation included sodium channel myotonia (SCM) (case 1), paramyotonia congenita (cases 2, 3, 4, 5, 7 and 8), and cold-aggravated myotonia (case 6) (case 6). Regarding the phenotype of hyperkalemic periodic paralysis, three probands described episodes of muscle weakness (cases 2, 4 and 9). Whole-cell recordings allowed to pinpoint the biophysical defects of L1436P. Thus, this mutation induced a significant slowing down of fast inactivation of the Nav current at several voltages, but this effect was less marked than in R1448H. The L1436P mutation also tended to induce a right shift in the steady-state inactivation curve, but only at cold temperature. On the other hand, a leftward shift in the activation curve was seen at cold and room temperatures with R1448H, but not L1436P. Recovery from fast inactivation was slowed down in both mutants, but only at cold temperature.DiscussionOur study confirms that the SCN4A-L1436P mutation can give rise to a spectrum of clinical presentations. Epigenetic alterations, modifying genes or environmental factors may influence clinical expression. Our experimental data indicates a relatively milder biophysical phenotype for L1436P as compared to R1448H, which becomes more pronounced at lower temperatures, consistent with the clinical phenotype of a majority of patients.